2,4-Epibrassinolide Mitigates Cd Stress by Enhancing Chloroplast Structural Remodeling and Chlorophyll Metabolism in Vigna angularis Leaves - Suyu Chen; Zihan Tang; Jialin Hou; Jie Gao; Xin Li; Yuxian Zhang; Qiang Zhao (Biology, 2025)
Cadmium (Cd) is a highly hazardous heavy metal that has an extensive impact throughout the world. 2,4-Epibrassinolide (BR) is an endogenous hormone that can enhance plant tolerance to various abiotic stresses. Herein, Vigna angularis cultivar “Zhen Zhuhong” was grown hydroponically and treated with 0, 1, and 2 mg·L−1 cadmium chloride (CdCl2) at the V1 stage, and foliar sprayed with or without 1 μM BR solution to analyze the effects of BR treatment on the physiology of Vigna angularis seedling leaves under Cd stress. BR treatment significantly alleviated the growth inhibition induced by Cd stress, which was associated with an increase in the plant height (11.15–17.83%), leaf area (35.59–56.72%), leaf dry weight (45.57–50.65%), and above-ground dry weight (50.86–55.17%). In addition, BR treatment induced significant reductions in Cd accumulation across different tissues of V. angularis, with decreases of 20.38–35.93% in leaves, 21.24–32.74% in stems, and 15.38–16.00% in petioles. Compared with the Cd treatment, BR treatment significantly enhanced the activities of peroxidase (5.02–13.22%), ascorbate peroxidase (27.13–70.28%), catalase (20.46–32.30%), and superoxide dismutase (16.54–21.81%), and increased the ascorbic acid content (27.55–45.52%), which contributed to a reduction in the accumulation of reactive oxygen species, cellular membrane damage, and cytoplasmic exosmosis. RNA-seq and real-time quantitative reverse transcription PCR analyses revealed that the BR treatment under Cd stress significantly upregulated the expression of genes involved in chlorophyll biosynthesis, transformation, and degradation, thereby enhancing the chlorophyll cycle. Furthermore, the BR treatment significantly increased the number of grana lamellae in the mesophyll cells, which enhanced the biosynthesis of chloroplasts. The increase in the chlorophyll content improved the capture of light energy, electron transport in photosynthesis, and the biosynthesis and metabolism of carbohydrates in the leaves of V. angularis under Cd stress.